(untitled) (Jurnal Intek Akuakultur, 2020)
The development of aquaculture biotechnology has supported many new findings such as hybrid fish for example the grouper fish and also to manipulate fish growth, such as through feed with a certain amount of protein and the administration of hormones such as prolactin, insulin and recombinant growth hormone (recombinant Growth Hormone / rGH). This study aims to determine the best dose and the effect of the hormone RGH on the growth and survival of the grouper fish abstraction.This study aims to determine the best dosage and the effect of rGH hormones on the growth and survival of bushy grouper seeds. This research was conducted in September 2018 for 45 days at the Household Scale Hachery in village of Pangkil, district of Bintan, Kepulauan Riau. The method used was experimental with Completely Randomized Design (CRD) with 3 treatments and 4 replications. Using data analysis with One-Way ANOVA showed that the administration of rGH hormone gave the best results in treatment B, which was given the hormone rGH at a dose of 24 mg / ℓ, where absolute weight growth (25.34 ± 10.04g), daily weight growth (0, 38 ± 0.06g / day), absolute length growth (3.80 ± 1.23cm), daily length growth (0.06 ± 0.01cm / day), survival (98.33 ± 2.89%), feed conversion ratio (3.12 ± 0.48) and feed efficiency level (35.23 ± 4.19%).